2016
DOI: 10.1093/cid/ciw365
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Antiretroviral Therapy During Acute HIV-1 Infection Leads to a High Rate of Nonreactive HIV Serology

Abstract: NCT00796146 and NCT00796263.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
93
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 37 publications
7
93
1
Order By: Relevance
“…Currently ongoing post-treatment control cohort studies focus on patients that start treatment very early after infection. Recent studies showed that the antibody response in patients that start in the earliest phase of acute infection in some cases not even develops [54]. Together with our data this study indicates that at least a certain extent of viral exposure is required for the selection of memory B cells that would give rise to a neutralizing antibody response.…”
Section: Discussionsupporting
confidence: 79%
“…Currently ongoing post-treatment control cohort studies focus on patients that start treatment very early after infection. Recent studies showed that the antibody response in patients that start in the earliest phase of acute infection in some cases not even develops [54]. Together with our data this study indicates that at least a certain extent of viral exposure is required for the selection of memory B cells that would give rise to a neutralizing antibody response.…”
Section: Discussionsupporting
confidence: 79%
“…Anti-HIV antibody levels decline when a patient is treated during primary HIV infection (PHI) and may not even develop to fulfill the criteria for HIV infection by standard confirmatory assays 1 . Recently, quantitative humoral profiling of the presumably “cured” Berlin patient revealed no antibodies to several HIV-1 antigens except reverse transcriptase (RT), Tat and gp41 2 .…”
Section: Introductionmentioning
confidence: 99%
“…As HIV RNA levels were either barely or non-detectable, the presence of antibodies to HIV-1 was suggested, although the confirmatory immunoassay (Multispot HIV 1/2) remained repeatedly non-reactive over 5 weeks. Delayed seroconversion may be observed in those administered cART during acute infection 18 and in one other case report of an individual becoming HIV-infected during repeated courses of post-exposure prophylaxis with TDF/FTC 19 . Essential to this case is that the combination of the reactive 4 th generation combination Ag/Ab test and the qualitative NAAT test established the diagnosis of HIV infection.…”
mentioning
confidence: 89%